Предмет:
МатематикаАвтор:
emma68Ответ: 6
Пошаговое объяснение:
По теореме Виета
x₁ + x₂ = -p,
p можно узнать из квадратного уравнения
x² + px + q = 0
x² + x - 6 = 0
p = 1
_________________________
x₁ + x₂ = -1
a = -1
a(x₁ * x₂) = b
x₁ * x₂ = -b
По теореме Виета
x₁ * x₂ = q
q = -6
Откуда -b = -6 ⇒ b = 6
Автор:
riosДобавить свой ответ
Предмет:
ИнформатикаАвтор:
philiponw4Ответов:
Смотреть
Предмет:
ЛитератураАвтор:
peteyud85Ответов:
Смотреть
Предмет:
ЛитератураАвтор:
heathОтветов:
Смотреть
Предмет:
ЛитератураАвтор:
laceyyldsОтветов:
Смотреть